ECO SUFISM: BENTUK RELASI TUHAN DAN ALAM DALAM MENJAGA LINGKUNGAN DARI KERUSAKAN - Nadi Nadi; Muhammad Arifin Guti Putra; Iffan Ahmad Gufron (Adisam Publisher, 2026)
This paper discusses eco-Sufism, a concept that bridges Islamic spirituality with environmental awareness. Amidst the global environmental crisis, an approach based on spirituality and ethics has become essential. Eco-Sufism views nature as a manifestation of God's beauty that must be preserved, adhering to the principle of wahdatul wujud, which sees the universe as a reflection of the Divine existence. Humans, as caliphs on earth, have a mandate to care for His creation with love. The biggest challenge for eco-Sufism today is materialistic lifestyles and secular views, but its growth potential is wide open through increased spiritual awareness and Islamic movements oriented towards environmental preservation. The implementation of eco-Sufism is reflected in a simple lifestyle and increased awareness of the importance of ecology, inspired by figures such as Rabi'ah al-Adawiyah and Jalaluddin Rumi, as well as the teachings of the Prophet Muhammad SAW.Eco-Sufism provides spiritual encouragement for concrete action in protecting the environment and combating the consumerist culture that exacerbates environmental damage. This approach invites us to feel connected to nature as part of a cosmic family under God's love, and encourages the emergence of a strong environmental ethic. This study seeks to present data and analysis that reinforce these ideas.